Analysis of Work Accident Risk Factors in Palm Tree Tapping Farmers or Arenga Pinnata Using Hazard Identification Risk Assessment and Risk Control Methods - Mhd. Nur Ridha Asshaf (Global Health Science Group, 2020)
Arenga pinnata Merr or aren is one of the species included in the family Aracaceae. In Indonesia the process of tapping aren still done traditionally using roughing tools. The purpose of this literature review is to find out the risk factors that can cause work accidents in palm tree tapping farmers. The sources used are from 20 PubMed NCBI, Google Schoolar, and Elsevier articles, and 20 articles used from 2013 to 2019. Of the 20 articles then analyzed using systematic literature review method, namely by collecting, evaluating, and developing research on the focus of a particular topic. The results of analysis of several articles found that fatigue at work, not using safety equipment at work, as well as poor weather, are very high risk factors and can lead to accidents in the work of palm tree tapping farmers.